(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
As Pakistan transitions to modernism, most women find themselves disadvantaged in the modern productivity sector while adhering to traditional cultural norms. The objectives of our study are to examine the lived experiences of salespeople in Pakistan and explore the intersection of modern workplace demands and patriarchal cultural norms. We applied qualitative research methodology and utilized elicit data from interviews with salesgirls employed in various supermarkets in Islamabad. We used thematic analysis technique to analyze the emerging themes from the collected data. Findings revealed that the sales girls working for the promotion of a product of the Multinational Companies are facing more challenges due to the demand for particular work attire than those working for the national companies or the supermarkets themselves. Those salesgirls faced isolation because of the cultural lag in Pakistani society’s traditional culture. Fathers and brothers of sale girls, find it difficult to accept the demands of modern work attire. Respondents suggested that MNCs should make better attire policies for salesgirls and other female workers that may resonate with their personal and cultural norms. Future researchers can use a mixed-method approach with an increased sample size for more comprehensive findings on the issue discussed in this research study.